Capacities of Extension Personnel within the Pluralistic System of Post-Conflict Liberia - Austen Moore; Amy Harder (Journal of International Agricultural and Extension Education, 2015)
Agricultural extension can play a major role in stimulating development, reducing hunger and poverty, and promoting stability in post-conflict Liberia. Consequently, the nation has prioritized extension to increase agricultural productivity and enhance livelihoods. However, the capacities of Ministry of Agriculture personnel and NGO workers have considerable impacts on the quality of extension services. This study sought to (a) describe the human resource capacity of Ministry of Agriculture personnel and NGO workers to deliver extension services to smallscale farmers, and (b) identify organizational barriers impacting the capacity of extension personnel. A qualitative design and purposive sampling were used, and the study included perspectives from 13 MoA and 16 NGO extensionists along with 39 farmers. Results showed MoA officers possessed lower technical and andragogical capacities than their NGO peers. Capacity deficiencies were especially acute among older MoA personnel employed prior to the conflict. Both the MoA and NGO sector advocated professional development, yet only larger international NGOs (INGOs) could provide these opportunities to their personnel. Inclusion of MoA and domestic NGO officers in INGO trainings helped develop basic capacities, although these opportunities were not maximized. Operational barriers such as high farmer-to-officer ratios, inadequate funding for extension programming, and challenges in modernizing the workforce further compromised officer capacity. Recommendations included prioritizing efforts to maximize the benefits of INGO trainings to the public sector, attracting skilled extensionists from the NGO sector to the MoA, incorporating and promoting younger officers and female extensionists to meet modern demands, and using low-cost methods to improve coverage.
Keywords: Human Resource Capacities; Organizational Barriers; Post-Conflict; Liberia